Dejavniki nizke stopnje zaupanja v Sloveniji - Iglič, Hajdeja (Družboslovne razprave, 2004)
Social capital in Slovenia is, in the comparison with Western European countries, rather low. This rises the question of the mechanisms of how to increase the social capital at the national level. In this article we study the impact of various factors on one specific aspect of social capital, on the generalized trust. On the basis of the analyses of the European Values Survey (1999-2000) and Citizenship, Involvement, Democracy (2002) data we show that Putnam's thesis about the positive effects of vibrant civil society and voluntary associations on generalized trust is not confirmed in the context of Slovenia. Instead, generalized trust is related to the high level of the satisfaction of life and optimism, post-materialist value orientation, and quality of public institutions. The most important institutional source of social capital is the degree of perceived fairness and impartiallity, and responsiveness to the public. There is a spillover from trust in institutions of the legal, educational, social security and health systems, and local government to the generalized trust. Political institutions and political actors are rather unimportant as a source of social capital, especially when compared to the impact of so called "street-level bureaucracy"
Keywords: civil society; civilna družba; družbena omrežja; socialni kapital; institucije; zaupanje